KELEMBAGAAN MUI DALAM MELAKUKAN GERAKAN HALALISASI: PERUBAHAN DINAMIKA MASYARAKAT DI PROV. KEP. BANGKA BELITUNG - Pebri Yanasari; Endang Kusniati (Scientia: Jurnal Hasil Penelitian, 2022)
Islam teaches people to consume halal and good food and drinks. The presence of this study aims to determine the strategy of LPPOM MUI Babel in carrying out concerns for halal-labeled products, and to determine the influence of LPPOM MUI on the dynamics of people's lives in Bangka Belitung. Qualitative and comparative descriptive methods are used in field research (Field research). Sources of data used come from primary and secondary data. While the data collection techniques with field observations and dissemination of google form links, unstructured interviews, and documentation. After the data is obtained, it is analyzed in three stages; data reduction (data reduction), data presentation (data display) and conclusions (conclusion). The phenomenological approach has been applied and strengthened by behavioristic theory. Based on the findings in the field, the LPPOM MUI Babel strategy: concern for halal-labeled products in general is appropriate, because it includes; INDHEX (Indonesia International Halal Expo), halal olympiad, halal food goes to school, halal tour (halal tour), seminar/talkshow, free halal certification facilitation, halal socialization to SMEs/big companies, halal socialization through media and social media, merchandise , and MUI administrators apply the principle of "buy and defend Babel halal products". While the influence of LPPOM MUI on the dynamics of people's lives in Bangka Belitung through halal product certification is still not significant in the field of using halal labeled products, this can be seen from the views of the pros and cons of the community when interviewed by researchers. However, based on the exposure of the Director of LPPOM MUI, it is quite significant at the level of "don't know to know", it means that people still don't understand what is halal. Keywords: MUI Institutionalization, halalization movement, community dynamics